2023
DOI: 10.1007/s00431-023-05343-z
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function using two dimension speckle-tracking echocardiography in children with celiac disease

Doaa El Amrousy,
Walid Elshehaby,
Radwa Elsharaby
et al.

Abstract: The prevalence of cardiac complications linked to celiac disease (CD) is on expanding. This study aimed to evaluate the cardiac function in children with CD using two dimensional speckle tracking echocardiography (2D-STE) to detect early myocardial dysfunction, if any. This cross-sectional study included 40 children with CD as the patient group and 40 healthy age- and sex-matched children served as the control group. High sensitive troponin T (Hs-troponin T), anti-tissue transglutaminase immunoglobulin A (tTG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Also, both intervention and control groups had normal LVEF [87]. Furthermore, El Amrousy et al showed that the LV global longitudinal strain was significantly lower in children affected by CD when compared to healthy individuals [88]. While advanced echocardiography imaging techniques have demonstrated superior diagnostic capabilities for cardiac dysfunction, it is noteworthy that the cases included in our study did not utilize these imaging modalities.…”
Section: Diagnosis and Testingmentioning
confidence: 67%
See 1 more Smart Citation
“…Also, both intervention and control groups had normal LVEF [87]. Furthermore, El Amrousy et al showed that the LV global longitudinal strain was significantly lower in children affected by CD when compared to healthy individuals [88]. While advanced echocardiography imaging techniques have demonstrated superior diagnostic capabilities for cardiac dysfunction, it is noteworthy that the cases included in our study did not utilize these imaging modalities.…”
Section: Diagnosis and Testingmentioning
confidence: 67%
“…This modality calculates regional and global myocardial deformation parameters such as strain and strain rate. Multiple studies have evaluated the usefulness of 2DSTE in the diagnosis of clinical or subclinical cardiac dysfunction in CD patients and have shown its superiority when compared to conventional TTE [86][87][88]. Cenk et al found that strain and strain rate imaging is superior to conventional TTE for the evaluation of cardiac involvement in CD.…”
Section: Diagnosis and Testingmentioning
confidence: 99%